A snapshot of parenting practices useful for preventing adolescent vaping - Hye Jeong Choi; Michelle Miller-Day; Michael Hecht; Shannon D. Glenn; Rachel E. Lyons; Kathryn Greene (Addictive Behaviors Reports, 2022)
Introduction: Smoking research demonstrates that parents can influence their adolescent’s tobacco smoking perceptions and behaviors, but little is known about the protective effects of different parenting practices on adolescent vaping. In this study we investigate how adolescent perceptions of parents’ knowledge of their activities and parental media mediation are associated with adolescents’ perceptions of vaping and adolescent vaping behaviors. Method: Six hundred thirty-nine youth (65.7% female, average age: 14.71 years old) recruited through 4-H clubs in nine states participated in a study evaluating a substance use intervention program. Because the evaluation design could influence participants, we used only baseline data. An online self-reported survey was administrated. Most youth self-identified as White (87.3%) and only handful youth indicated Asian (3.4%), African American (3.4%), American Indian (1.1%), and other or unreported (4.8%). Approximately 60% of youth lived in small town or rural areas in US. Results: Analyses revealed that parental knowledge was positively related with adolescent perceived harm of vaping and perceived prevalence of vaping, but was negatively related with perceived acceptability of vaping and social expectancy of vaping. In addition, youth who reported greater parental media mediation were more likely to perceive the harm of vaping and less likely to vape compared with youth with lower parental media mediation. Conclusion: These findings suggest that parental education about vaping, including those promoting conversations regarding vaping and vaping ads, may be important to the prevention of adolescent vaping.